Early selection for flowering time in almond breeding programs - Rubio M.; Cremades T.; Dicenta F. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Late flowering to reduce the risk of late frosts is one of the main objectives of the almond breeding programs. Breeders have to wait at least three years to know the flowering time of the seedlings, so it would be interesting to develop early selection strategies for this trait. Although some trials have been conducted correlating chilling requirements of seeds to germinate, leafing and flowering, the methodologies employed did not find a close correlation between these characteristics. In this work we studied the relationships between germination, sprouting and flowering in four families created in 2009 between very early and very late genitors that segregate well for flowering time. In winter, the seeds obtained were placed in imbibition for three days, removed the shell and stratified at 10°C in vermiculite for germination. Weekly the emergence of the root was noted as the date of germination. The plants obtained were taken to greenhouse in pots where they grew up till summer. Then they were taken to a cold room at 10°C, where weekly the number of buds sprouted was noted as the leafing time in controlled conditions. Finally, the plants were taken to the definitive plots and in 2013, 2014 and 2015 the leafing and flowering time were scored. Correlations between the requirements of seed to germinate and flowering time were no significant. Correlations between leafing time in the cold chamber and flowering time in the field several years later were intermediate, questioning the use of this correlation as early selection criterion for flowering time in almond.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)